Absorbent article

By introducing acid groups into starch or part of its decomposition, a water-soluble polymer is formed, which solves the problem of insufficient water absorption performance of existing water-absorbing resins, and improves water absorption performance and environmentally friendly reuse.

CN119630482APending Publication Date: 2025-03-14NAGASE & CO LTD +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380057433.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-01
Filing Date
2023-06-29
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing water-absorbing resins with polysaccharides as raw materials are not sufficiently absorbed and are difficult to meet certain application needs.

Method used

By introducing acid groups into starch or partially decomposed substances thereof to form a water-soluble polymer, a water-absorbent resin with excellent water-absorbent properties was prepared. The water-absorbent resin consists of acidic groups such as carboxyalkyl, carboxyalkenyl or sulfoalkyl introduced into starch or partially decomposed thereto.

Benefits of technology

A significant improvement in water absorption performance has been achieved, while the water-absorbing resin can be decomposed and reused, reducing the environmental burden.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005259975160000101
    Figure BDA0005259975160000101
  • Figure BDA0005259975160000102
    Figure BDA0005259975160000102
  • Figure BDA0005259975160000103
    Figure BDA0005259975160000103
Patent Text Reader

Abstract

Provided is an absorbent article containing a water-absorbent resin having excellent water absorption performance. The present invention relates to an absorbent article comprising a water-absorbent resin comprising a water-soluble polymer obtained by introducing an acidic group into starch or a partial decomposition product thereof.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to absorbent articles. Background Art

[0002] Absorbent articles are used in the fields of hygiene and medicine as diapers, sanitary products, wound protection materials, etc., and are also used in the fields of food, agriculture, forestry, civil engineering, etc. These absorbent articles exhibit liquid absorbency by containing water-absorbent resins. As water-absorbent resins, in addition to the widely used partially neutralized salts of polyacrylic acid and polymethacrylic acid, water-absorbent resins made of polysaccharides such as starch are also known.

[0003] Patent Document 1 discloses a method for producing a water-absorbent resin by heating and drying carboxyalkylated starch to crosslink the starches. It states that it is preferable to suppress a decrease in the molecular weight of the starch during the carboxyalkylation reaction.

[0004] Patent Document 2 discloses a method for producing a water-absorbing resin by surface-treating carboxyalkylated polysaccharide particles with a non-crosslinking acid such as hydrochloric acid and then crosslinking the polysaccharides by heat drying or by allowing a crosslinking agent to act.

[0005] Patent Document 3 discloses a method for producing a water-absorbing material by reacting starch with an anhydride of a polybasic acid in an extruder, and states that it is preferable to suppress a decrease in the molecular weight of starch during the reaction with the anhydride of a polybasic acid.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: U.S. Patent No. 5079354

[0009] Patent Document 2: Japanese Patent Application No. 2010-504414

[0010] Patent Document 3: Japanese Patent Application Laid-Open No. 2007-222704 Summary of the invention

[0011] Problems to be solved by the invention

[0012] The water absorption performance of conventional water-absorbent resins made of polysaccharides cannot be said to be sufficient. An object of the present invention is to provide an absorbent article comprising a water-absorbent resin having excellent water absorption performance.

[0013] Means for solving problems

[0014] The present inventors have studied the chemical structure of water-absorbent resins made of polysaccharides and have found a water-absorbent resin having excellent water absorption performance. The present invention has been completed by applying the water-absorbent resin to absorbent articles.

[0015] That is, the present invention relates to an absorbent article comprising a water-absorbent resin composed of a water-soluble polymer obtained by introducing an acidic group into starch or a partial decomposition product thereof.

[0016] The acidic group is preferably a carboxyalkyl group, a carboxyalkenyl group or a sulfoalkyl group.

[0017] The starch or its partial degradation product preferably has a weight average molecular weight (Mw) of 7,500,000 or less and / or a dispersion degree (weight average molecular weight (Mw) / number average molecular weight (Mn)) of 5 or more.

[0018] The pullulan-equivalent weight average molecular weight (Mw) of the water-soluble polymer obtained by aqueous size exclusion chromatography analysis is preferably 500,000 to 40,000,000.

[0019] The water-absorbent resin preferably has the following characteristics.

[0020] (a) the water absorption capacity of ion exchange water without pressure is 100 to 500 g / g;

[0021] (b) The water retention rate of ion exchange water is 80 to 300 g / g;

[0022] (c) the water absorption capacity of physiological saline under no pressure is 10 to 70 g / g; and / or

[0023] (d) The water retention rate of physiological saline is 5-60g / g.

[0024] The absorbent article is preferably any one selected from the group consisting of sanitary products, medical products, food preservation products, civil engineering products, and agricultural and gardening products.

[0025] The sanitary product is preferably any one selected from the group consisting of disposable diapers, sanitary products, incontinence pads, breast milk pads, portable toilets, and pet toilets.

[0026] The medical product is preferably any one selected from the group consisting of a hemostatic sponge, a wound protection material, a wound healing material, a medical waste solidifying agent, a cooling agent, a carrier for a drug delivery system, and an artificial joint.

[0027] Furthermore, the present invention relates to a regenerated water-soluble polymer obtained by subjecting the above-mentioned absorbent article to an alkali treatment.

[0028] Furthermore, the present invention relates to a water-absorbent resin which is a cross-linked product of the above-mentioned regenerated water-soluble polymer.

[0029] Furthermore, the present invention relates to a water-absorbent article comprising the water-absorbent resin.

[0030] The present invention also relates to a method for recovering hydrophilic fibers from an absorbent article comprising a water-absorbent resin and hydrophilic fibers, wherein the water-absorbent resin is composed of a water-soluble polymer obtained by introducing an acidic group into starch or a partial decomposition product thereof, wherein the method includes a step of subjecting a part or the whole of the water-absorbent article to an alkali treatment to decompose the water-absorbent resin.

[0031] Effects of the Invention

[0032] The water-absorbent article of the present invention has excellent water absorption performance. In addition, the water-absorbent resin made of polysaccharide as a raw material can be decomposed and reused, thereby reducing environmental burden. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The results of gel filtration chromatography of the water-soluble polymer are shown.

[0034] Figure 2 The infrared absorption spectrum of the water-soluble polymer is shown. DETAILED DESCRIPTION

[0035] <Absorbent articles>

[0036] The absorbent article of the present invention is characterized in that it contains a water-absorbent resin composed of a water-soluble polymer obtained by introducing an acidic group into starch or a partial decomposition product thereof.

[0037] <Starch or its partial degradation products>

[0038] In the present invention, starch or a partially decomposed product of starch is used as the main material of the water-absorbent resin. By using starch, a water-absorbent resin that is highly safe for the human body, has excellent water absorption, and has a small environmental burden when discarded can be obtained. The raw material of starch is not particularly limited, and examples thereof include cassava starch, potato starch, waxy corn starch, corn starch such as high-amylose starch, wheat starch, rice starch, sweet potato starch, etc. Partially decomposed products of starch are substances in which a part of the glycosidic bonds of a polymer formed by connecting multiple α-glucose molecules via glycosidic bonds are decomposed, and the location and manner of decomposition are not limited. The method for producing the water-absorbent resin will be described below, and starch and partially decomposed products of starch may also be used together when producing the water-absorbent resin.

[0039] When using a starch partial decomposition product, the weight average molecular weight (Mw) of the starch partial decomposition product is not particularly limited, preferably 7.5 million or less, more preferably 5 million or less, further preferably 4.5 million or less, and further preferably 4 million or less. The lower limit of the weight average molecular weight of the starch partial decomposition product is not particularly limited, preferably 50,000 or more, more preferably 100,000 or more, and further preferably 200,000 or more. If the weight average molecular weight is less than 50,000, there is a tendency that the water absorption of the water-absorbing resin decreases. In the case where the viscosity of the starch affects the operability in manufacturing, two or more starches and / or starch partial decomposition products with different weight average molecular weights, or other additives, etc. can also be used in combination according to the purpose and cost. It should be noted that the method for determining the weight average molecular weight is not particularly limited, and for example, it can be obtained by aqueous size exclusion chromatography based on a calibration curve of molecular weight and elution time made using pullulan with a known molecular weight.

[0040] The dispersity (weight average molecular weight (Mw) / number average molecular weight (Mn)) of the starch partial degradation product is not particularly limited, but is usually 5 or more. If it is less than 5, the water absorption of the water-absorbing resin tends to decrease. The upper limit of the dispersity is not particularly limited. The method for measuring the number average molecular weight is not particularly limited, and it can be obtained, for example, by aqueous size exclusion chromatography based on a calibration curve of molecular weight and elution time prepared using pullulan with a known molecular weight.

[0041] The weight average molecular weight and dispersity of starch or its partial degradation product are as described above. When starch is used alone, starch derived from waxy corn, cassava, corn, or potato is preferred, and starch derived from waxy corn, cassava, or corn is more preferred. When a partial degradation product of starch is used alone, its weight average molecular weight is preferably 50,000 to 7.5 million, more preferably 50,000 to 5 million, and even more preferably 100,000 to 4 million. In addition, the dispersity is preferably 5 or more, and more preferably 7 or more.

[0042] <Water-soluble polymer, acidic group>

[0043] The "water-soluble polymer" as used herein refers to a substance obtained by introducing an acidic group into starch or a partial decomposition product thereof.

[0044] Examples of the acidic group include acidic groups having a carboxyl group such as carboxyalkyl and carboxyalkenyl; acidic groups having a sulfonic group such as sulfoalkyl and sulfoalkenyl; and acidic groups having a phospho group such as phosphoalkyl and phosphoalkenyl.

[0045] The carboxyalkyl group is an alkyl group substituted with a carboxyl group. The number of carbon atoms of the alkyl group substituted with a carboxyl group is preferably 1 to 8, more preferably 1 to 5. The alkyl group may be either linear or branched. Specific examples of the alkyl group include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, 1-methyl n-butyl, 2-methyl n-butyl, 3-methyl n-butyl, 1,1-dimethyl n-propyl, 1,2-dimethyl n-propyl, 2,2-dimethyl n-propyl, 1-ethyl n-propyl, and the like.

[0046] Specific examples of the carboxyalkyl group include a carboxymethyl group, a carboxyethyl group, a carboxypropyl group, a carboxybutyl group, a carboxypentyl group, and the like.

[0047] The carboxyalkenyl group is an alkenyl group substituted with a carboxyl group. The number of carbon atoms of the alkenyl group substituted with a carboxyl group is preferably 2 to 8, more preferably 2 to 4. The alkenyl group may be any one of a straight chain and a branched chain. Specific examples of alkenyl groups include vinyl, 1-propenyl, 2-propenyl, 1-methyl-1-vinyl, 1-butenyl, 2-butenyl, 3-butenyl, 2-methyl-1-propenyl, 2-methyl-2-propenyl, 1-ethylvinyl, 1-methyl-1-propenyl, 1-methyl-2-propenyl, etc.

[0048] Specific examples of the carboxyalkenyl group include carboxyvinyl group, carboxypropenyl group, carboxybutenyl group and the like.

[0049] The sulfoalkyl group is an alkyl group substituted with a sulfo group. Examples of the alkyl group substituted with a sulfo group include the alkyl groups described above for the carboxyalkyl group. Specific examples of the sulfoalkyl group include a sulfomethyl group, a sulfoethyl group, a sulfopropyl group, and the like.

[0050] The sulfoalkenyl group is an alkenyl group substituted with a sulfo group. As the alkenyl group substituted with a sulfo group, the alkenyl group described with respect to the carboxyalkenyl group can be used. Specific examples of the sulfoalkenyl group include sulfovinyl group, sulfopropenyl group, and the like.

[0051] Phosphate alkyl is an alkyl group substituted with a phosphate group. As the alkyl group substituted with a phosphate group, the alkyl group described for the carboxyl alkyl group can be used. Specific examples of phosphate alkyl include methyl phosphate, ethyl phosphate, propyl phosphate, and the like.

[0052] The phosphoalkenyl group is an alkenyl group substituted with a phosphate group. As the alkenyl group substituted with a phosphate group, the alkenyl group described with respect to the carboxyalkenyl group can be used. Specific examples of the phosphoalkenyl group include phosphovinyl group, phosphoacryl group, and the like.

[0053] Among the acidic groups, acidic groups having a carboxyl group or a sulfo group are preferred from the viewpoint of ease of introduction into starch or its partial degradation product, carboxyalkyl groups, carboxyalkenyl groups, and sulfoalkyl groups are more preferred, and carboxyalkyl groups having 1 to 5 carbon atoms are further preferred.

[0054] In the water-soluble polymer, in addition to the acidic groups introduced into starch or its partial decomposition products, the hydrogen atoms of the hydroxyl groups of the glucose units may be substituted by functional groups other than the acidic groups. As the functional groups other than the acidic groups, for example, hydrocarbon groups such as methyl and ethyl, hydroxypropyl, hydroxyethyl and other substituents having hydroxyl groups may be cited. The position of the hydroxyl group substituted by the functional group other than the acidic group may be any of the 1st, 2nd, 3rd, 4th and 6th positions of the glucose unit, preferably the 2nd, 3rd and 6th positions.

[0055] The molecular weight of the water-soluble polymer is not particularly limited, and the weight average molecular weight of pullulan converted by aqueous size exclusion chromatography is preferably 500,000 to 40 million, more preferably 800,000 to 35 million. If the above weight average molecular weight is less than 500,000, the water absorption performance of the water-absorbing resin tends to decrease; if it is higher than 40 million, the viscosity is high and the handling properties in manufacturing tend to decrease. It should be noted that the weight average molecular weight of pullulan converted by aqueous size exclusion chromatography can be obtained based on a calibration curve of molecular weight and elution time made using pullulan with a known molecular weight in aqueous size exclusion chromatography.

[0056] The total acid value of the water-soluble polymer is preferably 50 to 350 mgKOH / g, more preferably 70 to 300 mgKOH / g. As described below, during the production of the water-absorbent resin, a portion of the salt of the acidic group added to the starch or the partially decomposed product of starch is neutralized, and the total acid value is the acid value measured by returning the neutralized acidic group to the unneutralized state, and represents the amount of all acidic groups possessed by the water-soluble polymer. If the total acid value is less than 50 mgKOH / g or more than 350 mgKOH / g, the water-absorbent resin after cross-linking the water-soluble polymer tends to have a reduced water absorption performance for an aqueous solution containing electrolytes such as saline.

[0057] In the case where a haloalkyl group having an acidic group is reacted with a hydroxyl group of starch to introduce an acidic group and prepare a water-soluble polymer, the amount of acidic group introduced can also be represented by the degree of etherification. The degree of etherification is preferably 0.1 to 2.0, more preferably 0.2 to 1.5. The degree of etherification can be obtained by ashing titration method, etc. In addition, the total acid value is detected by the introduction of acidic groups. In the case where the starch or starch partial decomposition product as the raw material does not contain acidic groups, it is considered that the acidic groups detected by the determination of the total acid value are equal to the acidic groups introduced by the etherification reaction. Therefore, in the case where there are no acidic groups in the starch or starch partial decomposition product of the raw material, the degree of etherification can be simply calculated by calculation from the numerical value of the above-mentioned total acid value. For example, in the case where the acidic group is a carboxymethyl group and all of them are neutralized as sodium salts, it can be calculated by degree of etherification = (162 × total acid value) ÷ (56100-80 × total acid value). It should be noted that the unit of the total acid value at this time is mgKOH / g.

[0058] The free acid value of the water-soluble polymer is preferably 5 to 50 mgKOH / g, more preferably 7 to 25 mgKOH / g. The free acid value refers to the acid value obtained by measuring the unneutralized acidic groups. If the free acid value is less than 5 mgKOH / g or more than 50 mgKOH / g, the water absorption performance of the water-absorbent resin tends to decrease.

[0059] The dispersity (weight average molecular weight / number average molecular weight) of the water-soluble polymer is not particularly limited, but is preferably 5 to 110, more preferably 7 to 70. If it is less than 5 or more than 110, the water absorption performance of the water-absorbent resin tends to decrease. The number average molecular weight of the water-soluble polymer can be determined based on a calibration curve of molecular weight and elution time prepared using pullulan with a known molecular weight in aqueous size exclusion chromatography.

[0060] <Crosslinking structure of water-absorbent resin>

[0061] Water-absorbent resins with polyacrylic acid as main structural units generally have a network structure based on covalent bonds and form chemical gels by absorbing water. In contrast, the water-absorbent resin used in the present invention is characterized in that it forms a physical gel by absorbing water. In a physical gel, crosslinking points are relatively easy to disappear due to thermal motion of molecular chains, changes in pH, ionic strength, etc., and can be converted into a sol with fluidity. Therefore, it is easy to decompose by adding alkali or acid, heating, shaking, etc., reducing the environmental burden when discarded.

[0062] The formation of a physical gel is determined by confirming the sol-gel transition caused by the disappearance of the crosslinking points. For example, in the case of crosslinking by ionic bonds and / or hydrogen bonds, it can be determined by fluidization after alkali or acid treatment. Specifically, when a water-absorbent resin is suspended in a 1% sodium hydroxide aqueous solution at a final concentration of 5% by weight and stirred for 60 minutes, and then sieved with a sieve with a mesh of 500 μm, if the dry weight of the water-absorbent resin remaining on the sieve is less than 2% by weight of the dry weight of the water-absorbent resin contained in the aqueous solution, it can be determined that a physical gel is formed by water absorption.

[0063] More specifically, 0.5 g of the water-absorbent resin was suspended in 9.5 g of a 1% sodium hydroxide aqueous solution and stirred for 60 minutes, and then naturally filtered using a 30-mesh metal mesh (mesh size 500 μm) of about 50 mm×50 mm square, and the mesh was washed with ion exchange water. After washing, the metal mesh was dried in a 120°C blower dryer for 2 hours. When the weight of the metal mesh before filtration is Wm1 and the weight of the metal mesh after filtration and drying is Wm2, if the 30-mesh sieve residue obtained by the following formula is less than 2% by weight, it can be determined that a physical gel is formed by absorbing water. It should be noted that the sieve with a mesh size of 500 μm is a 30-mesh sieve specified in JIS.

[0064] 30 mesh sieve residue (%) = (Wm2-Wm1) / 0.5×100

[0065] The 30-mesh sieve residue is preferably less than 2% by weight, more preferably less than 1.5% by weight, further preferably less than 1.0% by weight, and still further preferably less than 0.5% by weight.

[0066] The water-absorbent resin is a cross-linked product of the above-mentioned water-soluble polymer. Cross-linking includes internal cross-linking and optional surface cross-linking. However, the water-absorbent resin preferably does not have an internal cross-linking structure formed by an ether bond or an ester bond. In addition, the water-absorbent resin preferably does not have an internal cross-linking structure formed by a covalent bond. As the above-mentioned covalent bond, in addition to an ester bond and an ether bond, a carbon-carbon covalent bond, a double bond, etc. can also be cited. As the internal cross-linking structure constituting the water-absorbent resin, for example, an ionic bond formed by an acidic group on a water-soluble polymer and an acidic group to be neutralized, an ionic bond formed by a compound having an opposite charge to the water-soluble polymer (in the case where the acidic group of the water-soluble polymer is a carboxylic acid, a compound containing a basic group such as a cationic group or an amino group), an ionic bond formed by a divalent alkali metal ion, a coordination bond formed by a metal ion, a hydrogen bond such as dimerization of a carboxylic acid in the case where the acidic group is a carboxylic acid group, etc. can be cited. The formation method of the surface cross-linking is described later.

[0067] The water-absorbent resin may optionally contain structural units other than the above-mentioned water-soluble polymers. Examples of structural units other than water-soluble polymers include compounds having an opposite charge to that of the water-soluble polymer, such as chitosan, polyethyleneimine, polymers having amino groups such as vinylpyrrolidone-N,N-dimethylaminoethylmethacrylic acid copolymers or their salts, polymers having quaternary ammonium groups such as dimethylamine-epichlorohydrin copolymers and polydiallyldimethylammonium chloride. When the water-absorbent resin contains structural units other than water-soluble polymers, the content thereof is preferably 90% by weight or less, more preferably 50% by weight or less, relative to the total amount of the structural units and the water-soluble polymer used as the main component.

[0068] The water-absorbent resin may contain water and / or a hydrophilic solvent. Examples of the hydrophilic solvent include methanol, ethanol, n-propanol, isopropanol, acetone, ethylene glycol, propylene glycol, diethylene glycol, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol dimethyl ether, dimethyl sulfoxide, and the like. The content of water and / or a hydrophilic solvent in the water-absorbent resin is preferably 0.1 to 20%, more preferably 1 to 19%. If it is less than 0.1%, the water absorption rate tends to decrease; if it is more than 20%, the water-absorbent resin particles tend to easily aggregate when absorbing water. The content of water and / or a hydrophilic solvent can be adjusted by subjecting the water-absorbent resin to treatments such as heating and drying.

[0069] <Physical Properties of Water-Absorbent Resin>

[0070] The water absorption rate of the water-absorbent resin without pressure is determined by measuring the absorbency of physiological saline or ion exchange water when no load is applied to the water-absorbent resin by the method described in the Examples. The water absorption rate of the water-absorbent resin used in the present invention for ion exchange water without pressure in the state of a solid substance is preferably 100 to 500 g / g, more preferably 100 to 400 g / g, and further preferably 120 to 350 g / g. In addition, the water absorption rate of the water-absorbent resin used in the present invention for physiological saline without pressure is preferably 10 to 70 g / g, and more preferably 20 to 65 g / g.

[0071] The ratio (A / B) of the water-absorbent resin's absorption capacity (A) for ion-exchanged water to its absorption capacity (B) for physiological saline is preferably 7 or less, more preferably 5 or less.

[0072] The water retention rate of the water-absorbent resin is determined by measuring the absorbency of the water-absorbent resin for saline or ion-exchanged water when a load of 150 G is applied to the water-absorbent resin by the method described in the Examples. The water retention rate of the water-absorbent resin of the present invention for ion-exchanged water in the state of a solid substance is preferably 80 to 300 g / g, more preferably 100 to 250 g / g. In addition, the water retention rate of the water-absorbent resin of the present invention for saline is preferably 5 to 60 g / g, more preferably 10 to 60 g / g, and even more preferably 20 to 60 g / g.

[0073] <Method for producing water-absorbent resin>

[0074] As long as the water-absorbent resin has the above-mentioned structure, its production method is not particularly limited, and it can be obtained, for example, by a process of forming an internal cross-linked structure in starch or its partially decomposed product. In addition, before the process of forming the internal cross-linked structure, a process of partially decomposing starch and / or a process of introducing acidic groups may be included as needed. It should be noted that when a process of partially decomposing starch and a process of introducing acidic groups are included, the order of these processes is different, and any one of the processes may be performed first.

[0075] In the process of partially decomposing starch, the α-1,4-glycosidic bonds of the α-glucose molecules constituting starch are decomposed in most cases, but the location and method of decomposition are not limited. The decomposition method is not particularly limited, and examples include enzyme treatment, acid treatment, physical crushing, and the like. These methods may also be combined. The enzyme treatment may be performed after starch gelatinization or simultaneously with gelatinization. As a method for performing enzyme treatment after starch gelatinization, a method may be mentioned in which the starch is first gelatinized by suspending it in water and heating it, and then adding an enzyme to perform an enzyme reaction. In addition, as a method for performing enzyme treatment simultaneously with the gelatinization of starch, a method may be mentioned in which the starch is suspended in water, an enzyme is further added, and the resulting mixed solution is heated in a temperature range in which the enzyme is not completely inactivated. Among them, it is preferred to heat and knead the starch at 70 to 110°C and perform enzyme treatment while gelatinizing.

[0076] In the case of partial decomposition of starch by enzyme treatment, the enzyme used is not particularly limited as long as it can decompose starch, and can be any of an exo-type enzyme and an endo-type enzyme. As a specific example of an enzyme, α-amylase, amylomaltase, cyclomaltodextrin glucanotransferase, 4-α-glucanotransferase, 4,6-α-glucanotransferase, neopullulanase, amyloplulanase, etc. can be cited. These enzymes can also be used in combination. The pH during enzyme treatment is not particularly limited, preferably pH 5.0 to 7.0. The adjustment of pH can be carried out by adding hydrochloric acid, acetic acid, sodium hydroxide, potassium hydroxide, etc.

[0077] When starch is partially decomposed by acid treatment, the acid used is not particularly limited as long as it can decompose starch, and specific examples include hydrochloric acid, sulfuric acid, oxalic acid, acetic acid, formic acid, trifluoroacetic acid, etc. The temperature during the acid treatment is preferably 150 to 160°C.

[0078] When partial decomposition of starch is performed by physical disruption, specific means include radiation irradiation, shearing, grinding, high pressure treatment, ultrasonic wave, thermal decomposition, photodecomposition, and combinations thereof.

[0079] Starch or its partial decomposition product may also be a derivative (also called processed starch or chemical starch) or bleached starch in which the hydrogen atom of the hydroxyl group of the glucose unit is replaced by a functional group. The position of the hydroxyl group in which the hydrogen atom is replaced may be any of the positions 1, 2, 3, 4, and 6 of the glucose unit, preferably the positions 2, 3, and 6. As the functional group, for example, hydrocarbon groups such as methyl and ethyl groups; substituents having a hydroxyl group such as hydroxypropyl and hydroxyethyl groups; substituents having a carboxyl group such as carboxylmethyl groups, etc. As examples of derivatives of starch or its partial decomposition product, acetylated adipic acid cross-linked starch, acetylated phosphorylated cross-linked starch, acetylated oxidized starch, sodium octenyl succinate starch, acetic starch, oxidized starch, hydroxypropyl starch, hydroxypropyl phosphoric acid cross-linked starch, phosphoric acid monoesterified phosphoric acid cross-linked starch, phosphorylated starch, phosphoric acid cross-linked starch, cationized starch, urea phosphoric acid esterified starch, etc. may be mentioned. In addition, methyl ethylated starch and hydroxypropyl methylated starch substituted with two or more functional groups may also be used. Among these, acetic acid starch, oxidized starch, hydroxypropyl starch, and sodium starch octenylsuccinate are preferred from the viewpoint of easiness of controlling the properties of the water-absorbing resin.

[0080] When starch or its partial degradation product is a derivative in which the hydrogen atoms of the hydroxyl groups of the glucose unit are substituted with acidic groups, a step of introducing acidic groups may be performed to further add acidic groups, or a step of forming an internal crosslinked structure may be performed without performing the step of introducing acidic groups.

[0081] In the step of introducing the acidic group, starch or a starch partial decomposition product is reacted with a compound containing an acidic group or a precursor thereof. Through this reaction, an acidic group is introduced into the hydroxyl group of starch or a starch partial decomposition product. The compound containing an acidic group is not particularly limited as long as the above-mentioned acidic group can be introduced, and examples thereof include halogenated alkyl compounds having an acidic group, halogenated alkenyl compounds having an acidic group, acid anhydrides, and salts thereof. As halogens constituting the halogenated alkyl compounds and halogenated alkenyl compounds, chlorine and bromine can be mentioned.

[0082] Specific examples of compounds containing an acidic group include monochloroacetic acid, monobromoacetic acid, 3-bromopropionic acid, 6-bromohexanoic acid, succinic anhydride, maleic anhydride, vinylsulfonic acid, phosphorus oxychloride, ethyl monochloroacetate, and sodium salts and potassium salts thereof. Specific examples of salts include sodium monochloroacetate, potassium monochloroacetate, and sodium vinylsulfonate.

[0083] Precursors of compounds containing an acidic group include acrylonitrile, etc. Examples of methods for using acrylonitrile include the following method: first, acrylonitrile is reacted with starch or a partial decomposition product thereof under alkaline conditions to introduce a cyanoethyl group, the cyanoethyl group is derived into an amide group (Synthesis; 1989 (12): 949-950), and then the obtained amide is subjected to alkaline hydrolysis.

[0084] The outline of the reaction of generating a water-soluble polymer by the reaction of starch or a partially degraded product of starch with monochloroacetic acid is shown in formula (I).

[0085] [Chemistry 1]

[0086]

[0087] The general outline of the reaction of generating a water-soluble polymer by the reaction of starch or a partially degraded product of starch with 3-bromopropionic acid is shown in formula (II).

[0088] [Chemistry 2]

[0089]

[0090] The outline of the reaction of generating a water-soluble polymer by the reaction of starch or a partially degraded product of starch with 6-bromohexanoic acid is shown in formula (III).

[0091] [Chemistry 3]

[0092]

[0093] The outline of the reaction of generating a water-soluble polymer by the reaction of starch or a partially degraded product of starch with succinic anhydride is shown in formula (IV).

[0094] [Chemistry 4]

[0095]

[0096] The general outline of the reaction of generating a water-soluble polymer by the reaction of starch or a partially degraded product of starch with maleic anhydride is shown in formula (V).

[0097] [Chemistry 5]

[0098]

[0099] The outline of the reaction of generating a water-soluble polymer by reacting starch or a partially decomposed product of starch with sodium vinyl sulfonate is shown in formula (VI).

[0100] [Chemistry 6]

[0101]

[0102] Formulas (I) to (VI) show water-soluble polymers in which a sodium salt of an acidic group is introduced into all the hydroxyl groups at the 6-position of the glucose unit, but a hydroxyl group into which an acidic group is not introduced may remain. In addition, an acidic group that is not neutralized by a salt may also exist. The position where the acidic group is introduced is not limited as long as it is a hydroxyl group present in starch or a partially decomposed product of starch, and may be any of the hydroxyl groups at the 1-position, 2-position, 3-position, 4-position, and 6-position.

[0103] When a haloalkyl compound or a haloalkenyl compound is used as a compound containing an acidic group, it is preferred to use an alkaline agent in an amount of 1 to 1.5 equivalents relative to the haloalkyl compound or the haloalkenyl compound. As alkaline agents, sodium hydroxide, potassium hydroxide, lithium hydroxide, ammonia, sodium carbonate, potassium carbonate, etc. can be cited. The acidic group introduced into starch or a partial decomposition product of starch preferably forms a salt with sodium, potassium, lithium, ammonia, etc. from an alkaline agent, so the alkaline agent is preferably used in the amount required for the reaction of the haloalkyl compound or the haloalkenyl compound with starch or its partial decomposition product, and the neutralization of the acidic group of the haloalkyl compound or the haloalkenyl compound. For example, when chloroacetic acid is used as a compound containing an acidic group, the alkaline agent is theoretically preferably used in an amount of 2 or more equivalents relative to chloroacetic acid. When sodium chloroacetate is used, the acidic group is neutralized in advance, so the alkaline agent is preferably used in an amount of 1 or more relative to sodium chloroacetate.

[0104] The amount of the compound containing an acidic group can be arbitrarily set according to the target total acid value (etherification degree) of the water-soluble polymer. Usually, it is preferably 0.5 to 5.0 equivalents, more preferably 0.5 to 2 equivalents, relative to 1 mol of hydroxyl groups of starch or a partially decomposed product of starch. In the case of using a haloalkyl compound such as chloroacetic acid to react in the form of an aqueous solution, the haloalkyl compound needs to be in excess than the theoretical amount because the introduction reaction of the acidic group competes with the hydrolysis reaction of the haloalkyl compound. The amount of the haloalkyl compound in the aqueous solution reaction is preferably set to 5 equivalents or less relative to the theoretical value.

[0105] The reaction temperature of starch or starch partial decomposition product and the compound containing acidic group is not particularly limited, and is preferably 0 to 120°C. The reaction time is not particularly limited, and is preferably 1 to 24 hours. The reaction can be carried out in water, or in a mixed solvent of water and alcohols such as methanol, ethanol, isopropanol, butanol, ethylene glycol, diethylene glycol, propylene glycol, ethylene glycol monoethyl ether, glycol ethers such as ethylene glycol dimethyl ether, etc., or the powder of the dried starch partial decomposition product can be dispersed in a hydrophilic solvent such as alcohols such as methanol, ethanol, isopropanol, butanol, glycol ethers such as ethylene glycol dimethyl ether, etc. When a mixed solvent is used, the proportion of solvents other than water in the mixed solvent is preferably less than 50% by volume. As a reaction apparatus, a reactor, an extruder, etc. can be used.

[0106] When a halogenated alkyl compound such as chloroacetic acid or a salt thereof is used as the acidic group-containing compound, the reaction temperature with starch or a partially decomposed product of starch is not particularly limited, but is preferably 0 to 100°C.

[0107] In particular, when chloroacetic acid or its salt is used as the halogenated alkyl compound, in order to prevent hydrolysis caused by water in the reaction solution, it is preferably carried out at 25 to 90°C. The reaction time is preferably the time until the halogenated alkyl compound as the raw material is consumed, and for the stability of the halogenated alkyl compound and the efficiency of the process, 1 to 12 hours is more preferred. The reaction can be carried out in water, or in a mixed solvent of water and alcohols such as methanol, ethanol, isopropanol, butanol, glycol ethers such as ethylene glycol dimethyl ether, etc., or the powder of the dried starch partial decomposition product can be dispersed in a hydrophilic solvent such as alcohols such as methanol, ethanol, isopropanol, butanol, glycol ethers such as ethylene glycol dimethyl ether, etc. When a mixed solvent is used, the proportion of solvents other than water in the mixed solvent is preferably less than 50% by volume. As a reaction apparatus, a reactor, an extruder, etc. can be used.

[0108] In addition, when anhydride is used as the compound containing an acidic group, the reaction can be carried out by mixing the starch partial decomposition product with the anhydride and heating it, but in order to promote the reaction, tertiary amines such as sodium carbonate, sodium hydroxide, triethylamine, imidazoles such as 2-methylimidazole, quaternary ammonium salts such as tetrabutylammonium bromide, and phosphonium salts such as tetrabutylphosphonium bromide can be used as catalysts. The addition amount of these catalysts is preferably less than 0.1 equivalent relative to the compound containing an acidic group. These catalysts can be used alone or in combination of two or more.

[0109] The reaction time is preferably the time until the acid anhydride as the raw material is consumed, and more preferably 1 to 12 hours. The end point of the reaction can be determined by acid value determination and IR determination. The reaction can be carried out in water, but in order to prevent hydrolysis and alcoholysis of the acid anhydride, the reaction solvent is preferably a non-protonic solvent such as dimethyl sulfoxide, dimethylformamide, dimethylacetamide, N-methylpyrrolidone. When a mixed solvent is used, the proportion of solvents other than water is preferably 50% by volume or more in the mixed solvent. When the reaction is carried out under solvent-free conditions, the acid anhydride can play the role of a solvent, so the reaction temperature is preferably carried out above the melting point of the acid anhydride. When a solvent is used in the reaction, the reaction temperature is preferably 50 to 100°C, more preferably 70 to 90°C. As a reaction apparatus, a reactor, an extruder, etc. can be used.

[0110] The salt of the acidic group added to the starch or the starch partial decomposition product is preferably partially neutralized. By neutralization, a part of the acidic group that has formed the salt is converted into a free acidic group. For example, when monochloroacetic acid is used as the above-mentioned acidic group-containing compound and sodium hydroxide is used as the alkaline agent, a sodium salt of a carboxyl group is added to the starch or the starch partial decomposition product. By adding an acid thereto, a part of the carboxyl group is converted into a free carboxylic acid.

[0111] The acid used for neutralization is not particularly limited. When the acidic group is a carboxyl group, an acid having a pKa equal to or lower than that of the carboxyl group is preferred, and examples thereof include hydrochloric acid, sulfuric acid, phosphoric acid, nitric acid, acetic acid, formic acid, trichloroacetic acid, and the like. Strong acids are preferably used for neutralization of sulfonic or phosphoric acid groups, and inorganic acids such as hydrochloric acid and sulfuric acid, and strongly acidic ion exchange resins are used. Neutralization can be carried out using known devices such as a reactor and an extruder. After the addition of the acid, it is preferably stirred at 0 to 50° C. for 0.2 to 1 hour in order to carry out the neutralization reaction. The neutralization reaction is preferably carried out under the conditions of pH 6.8 to 7.2.

[0112] In the process of introducing the acidic group and the subsequent neutralization reaction, the halogen from the compound containing the acidic group may form a salt with the metal and ammonia from the alkaline reagent, so it is preferred to perform desalination. As a desalination method, a method of cleaning by the following process can be cited: a water-soluble polymer is dissolved in water to prepare an aqueous solution, and the aqueous solution is added dropwise to a hydrophilic solvent such as methanol, ethanol, isopropanol, acetone, acetonitrile, etc., so that the water-soluble polymer is reprecipitated, filtered and recovered, and then the filtered and recovered water-soluble polymer is dispersed again in aqueous methanol (water content of about 70 to 90%), and after stirring, the particles of the water-soluble polymer are filtered and recovered. In addition, as a desalination method, a method of treating an aqueous solution of a hydrophilic polymer using a filter with an ultrafiltration membrane can be cited. As a cleaning solution during desalination, water, a mixed solution of water and a hydrophilic organic solvent such as methanol, ethanol, propanol, acetone, acetonitrile, etc. can be used. Desalination is preferably carried out until the salt concentration in the water-soluble polymer reaches less than 1%.

[0113] In the process of forming the internal crosslinked structure, the water-soluble polymers are crosslinked with each other. The crosslinking can be formed without using a crosslinking agent, for example, by a method of heating and drying a water-soluble polymer in which a part of the acidic groups is a free acidic group under aqueous conditions. The temperature during heating and drying is preferably 50 to 150° C., more preferably 60 to 130° C. The air pressure during heating and drying is not particularly limited, and it can be carried out under normal pressure, specifically, it is preferably carried out under 0.9 to 1.1 atmospheres. The drying method is not particularly limited, and it can be carried out using a drum dryer, a spray dryer, a Nauta mixer, etc.

[0114] During heat drying, the water-soluble polymer may contain a hydrophilic solvent in addition to water. Examples of the hydrophilic solvent include lower aliphatic alcohols such as methanol, ethanol, n-propanol and isopropanol; ketones such as acetone; ethers such as dioxane, tetrahydrofuran and methoxy (poly)ethylene glycol; amides such as ε-caprolactam and N,N-dimethylformamide. The proportion of the hydrophilic solvent other than water in all solvents is preferably adjusted according to the boiling point of the solvent. When the boiling point of the solvent is below 100°C, it is preferably 70% by volume or more, and when it is above 100°C, it is preferably 30% by volume or less. In addition, the water-soluble polymer at the time of starting heat drying may be an aqueous solution or a powder containing an aqueous solvent with a water content of 1% or more. When drying a powder containing an aqueous solvent, the moisture content of the powder at the start of drying is preferably 1 to 85% by weight, more preferably 20 to 80% by weight, and further preferably 55 to 75% by weight. It should be noted that the moisture ratio referred to herein refers to the ratio of the total amount of water and the hydrophilic solvent in the powder.

[0115] In the manufacture of water-absorbent resin, in addition to internal crosslinking, surface crosslinking can also be performed. By surface crosslinking, the strength of the water-absorbent resin can be improved. As the crosslinking agent used for surface crosslinking, epoxy compounds, polyol compounds, polyamine compounds, polyisocyanate compounds, alkylene carbonate compounds, halogenated epoxy compounds, halohydrin compounds, polyoxazoline compounds, carbodiimide compounds, silane coupling agents, polyvalent metal compounds, etc. can be cited.

[0116] Examples of the epoxy compound include glycidyl succinate, sorbitol polyglycidyl ether, trimethylolpropane polyglycidyl ether, polyethylene glycol diglycidyl ether, glycerol polyglycidyl ether, diglycerol polyglycidyl ether, polyglycerol polyglycidyl ether, propylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, and glycidol.

[0117] Examples of the polyol compound include ethylene glycol, diethylene glycol, propylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycol, 1,3-propylene glycol, dipropylene glycol, 2,2,4-trimethyl-1,3-pentanediol, polypropylene glycol, glycerol, polyglycerol, 2-butene-1,4-diol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,2-cyclohexanedimethanol, 1,2-cyclohexanediol, trimethylolpropane, diethanolamine, triethanolamine, polyoxypropylene, ethylene oxide-propylene oxide block copolymer, pentaerythritol, and sorbitol.

[0118] Examples of the polyamine compound include ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, polyethyleneimine, and inorganic or organic salts (azetinium salts, etc.) of these polyamine compounds.

[0119] Examples of the polyisocyanate compound include 2,4-toluene diisocyanate and hexamethylene diisocyanate, and examples of the polyoxazoline compound include 1,2-ethylenebisoxazoline.

[0120] Examples of the alkylene carbonate compound include 1,3-dioxolane-2-one, 4-methyl-1,3-dioxolane-2-one, 4,5-dimethyl-1,3-dioxolane-2-one, 4,4-dimethyl-1,3-dioxolane-2-one, 4-ethyl-1,3-dioxolane-2-one, 4-hydroxymethyl-1,3-dioxolane-2-one, 1,3-dioxane-2-one, 4-methyl-1,3-dioxane-2-one, and 4,6-dimethyl-1,3-dioxane-2-one.

[0121] Examples of the halogenated epoxy compound include epichlorohydrin, epibromohydrin, α-methylepichlorohydrin, and polyamine adducts thereof (for example, Kymene (registered trademark) manufactured by Hercules Corporation).

[0122] In addition, as other known cross-linking agents, aqueous carbodiimide compounds (for example, Carbodilite manufactured by Nisshinbo Chemical Co., Ltd.), silane coupling agents such as γ-glycidoxypropyltrimethoxysilane and γ-aminopropyltriethoxysilane, and polyvalent metal compounds such as hydroxides or chlorides of zinc, calcium, magnesium, aluminum, iron, zirconium, etc. can also be used.

[0123] Among these, epoxy compounds are preferred, and ethylene glycol diglycidyl ether, sorbitol polyglycidyl ether, and glycidyl succinate are more preferred.

[0124] The surface crosslinking can be formed by spraying the surface crosslinking agent onto the water-absorbent resin and mixing it by a known method using a cylindrical mixer, a V-shaped mixer, a ribbon mixer, a screw mixer, a double-arm mixer, a pulverizing kneading machine, etc. A surfactant can be added as needed during the spraying and mixing.

[0125] In addition, in order to impart various functions, the water-absorbent resin may contain other additives such as disinfectants, deodorants, antibacterial agents, fragrances, various inorganic powders, foaming agents, pigments, dyes, hydrophilic short fibers, fertilizers, oxidants, reducing agents, water, and salts. The amounts of these additives may be appropriately selected by those skilled in the art.

[0126] <Uses of absorbent articles>

[0127] The absorbent article of the present invention can be used as sanitary products, medical products, civil engineering products, food preservation products, agricultural and gardening products, and the like.

[0128] The absorbent article of the present invention can absorb and retain liquids containing proteins, so in sanitary and medical applications, in addition to absorbing and retaining urine, it can also be used to absorb and retain blood, menstrual blood, breast milk, etc. containing proteins. Specific sanitary products include diapers, sanitary products, incontinence pads, breast milk pads, facial masks, portable toilets, pet toilets, cat litter, etc. Medical products include hemostatic sponges (medical pads), wound protection materials, wound healing materials, medical waste solidifiers, cold preservation agents, carriers for drug delivery systems, artificial joints, wet compress materials, etc.

[0129] Examples of food preservatives include cooling agents, cooling gels, water-retaining materials, anti-condensation sheets, droplet absorbers, and preservatives.

[0130] Examples of civil engineering products include waterproofing materials, waste liquid solidifying agents, residual soil solidifying agents, and anti-condensation building materials.

[0131] Examples of agricultural and horticultural products include soil conditioners, soil water-retaining materials, seedling pots, seedbeds, hydroponic supports, fertilizer-retaining materials, and slow-release agents for fertilizers.

[0132] Other uses include thickeners for fragrances, disposable heat pads, portable toilets, and cosmetics.

[0133] <Diapers, sanitary napkins>

[0134] The absorbent article of the present invention may have a structure suitable for various uses as long as it contains the above-mentioned water-absorbent resin. For example, when the absorbent article is made into a diaper or sanitary napkin, the diaper or sanitary napkin is composed of a laminated body in which a top sheet, an absorbent body and a back sheet are laminated in this order.

[0135] The top sheet is a sheet that contacts the body of the wearer when the diaper or sanitary napkin is worn. The top sheet is preferably liquid-permeable, and a hydrophilic nonwoven fabric, a porous resin film, etc. can be used. The back sheet is a sheet that does not contact the body of the wearer when the diaper or sanitary napkin is worn and is located on the outside. The back sheet is preferably liquid-impermeable, and a hydrophobic nonwoven fabric, a resin film, a laminate of a nonwoven fabric and a resin film, etc. can be used.

[0136] The absorbent body includes the water-absorbing resin described above. The absorbent body may be a molded body formed by molding the water-absorbing resin into a predetermined shape. Alternatively, the water-absorbing resin may be packaged with a core material and used as the absorbent body. As the core material, a paper sheet or a liquid-permeable nonwoven fabric may be used.

[0137] In addition to the above-mentioned water-absorbent resin, the absorbent body may also include natural hydrophilic fibers such as absorbent paper, pulp, acetate, tissue paper, hydrophilic nonwoven fabrics, cotton, etc., hydrophilic fibers of natural origin based on cellulose such as lyocell, rayon, and cuprammonium fiber, hydrophilic fibers of petroleum origin obtained by treating acrylic fiber, polyacrylic acid series, polyaspartic acid series, starch·acrylonitrile series, etc. water-absorbent resins. The proportion of the water-absorbent resin composed of a water-soluble polymer formed by introducing an acidic group into starch or its partial decomposition product in the absorbent body is preferably 35% by weight or more, more preferably 40% by weight or more in the case of diapers. In the case of sanitary napkins, it is preferably 5% by weight or more, more preferably 10% by weight or more. In the case of both diapers and sanitary napkins, the upper limit is not particularly limited and is 100% by weight or less.

[0138] When the absorbent body contains the hydrophilic fibers, the content thereof is preferably 10 to 500 parts by weight, more preferably 20 to 300 parts by weight, based on 100 parts by weight of the water-absorbent resin.

[0139] <Regenerated water-soluble polymer>

[0140] The regenerated water-soluble polymer is obtained by subjecting the absorbent article or the water-absorbent resin contained in the absorbent article to an alkali treatment. During the alkali treatment, the absorbent article or the water-absorbent resin contained in the absorbent article is placed under conditions of preferably pH 9.0 or higher, more preferably pH 10.0 or higher. The alkali treatment cleaves the cross-linked structure or glycosidic bond of the water-absorbent resin and decomposes it into a water-soluble polymer, which can reduce the environmental burden when it is discarded.

[0141] The alkaline agent used in the alkali treatment is not particularly limited, and examples thereof include sodium hydroxide, potassium hydroxide, lithium hydroxide, ammonia, sodium carbonate, potassium carbonate, etc. In the case of using an alkaline aqueous solution for alkali treatment, the concentration of the alkaline agent in the aqueous solution is preferably 0.01 to 20% by weight, more preferably 0.1 to 5% by weight. The temperature during the alkali treatment is not particularly limited, and for example, it can be carried out under conditions of 5 to 70° C. The time for the alkali treatment is preferably 1 to 120 minutes. The regenerated water-soluble polymer can be neutralized, concentrated, washed, filtered, etc. by adding acid as needed after the alkali treatment. The regenerated water-soluble polymer preferably has the molecular weight, dispersity, total acid value, free acid value, and dispersity described above for the water-soluble polymer.

[0142] By cross-linking the regenerated water-soluble polymer, a water-absorbent resin can be obtained. The cross-linking method and cross-linking structure of the regenerated water-soluble polymer are preferably the cross-linking method and cross-linking structure described above for the water-soluble polymer. The water-absorbent resin obtained by cross-linking the regenerated water-soluble polymer preferably has the physical properties of the water-absorbent resin described above. The water absorption rate of ion exchange water without pressure, the water retention rate of ion exchange water, the water absorption rate of physiological saline without pressure, and the water retention rate of physiological saline of the water-absorbent resin obtained by cross-linking the regenerated water-soluble polymer are preferably 60 to 140%, more preferably 80 to 120%, further preferably 90 to 110%, and particularly preferably 95 to 105% respectively relative to the same water absorption characteristics of the water-absorbent resin obtained by cross-linking the non-regenerated water-soluble polymer.

[0143] The absorbent article can be obtained by crosslinking the water-absorbent resin obtained by regenerating the water-soluble polymer. The structure and use of the absorbent article are as described above.

[0144] <Method for recovering hydrophilic fibers>

[0145] The method for recovering hydrophilic fibers of the present invention is a method for recovering hydrophilic fibers from an absorbent article comprising a water-absorbent resin and hydrophilic fibers, wherein the water-absorbent resin is composed of a water-soluble polymer obtained by introducing an acidic group into starch or a partial decomposition product thereof, and the method is characterized in that it includes a step of subjecting a part or the whole of the water-absorbent article to an alkali treatment to decompose the water-absorbent resin.

[0146] As the water-absorbent resin, hydrophilic fiber, and absorbent article, the above-mentioned water-absorbent resin, hydrophilic fiber, and absorbent article can be used. In the process of decomposing the water-absorbent resin, the object of alkali treatment can be all the water-absorbent articles or part of the water-absorbent articles. In the case of alkali treatment of a part of the water-absorbent articles, the treatment object includes the water-absorbent resin and the hydrophilic fiber. The alkali treatment conditions can use the conditions described for the regenerated water-soluble polymer. By alkali treatment of a part or all of the water-absorbent articles, the water-absorbent resin is decomposed and dissolved, and the hydrophilic fiber is obtained in the form of a solid residue. The hydrophilic fiber obtained in the form of a solid residue in the process of decomposing the water-absorbent resin is then dried, and after dissociation and fiber opening as needed, it can be used in the manufacture of absorbent articles such as diapers in the same way as virgin pulp. In addition, in addition to being used in water-absorbent articles, the recovered hydrophilic fiber can also be used for purposes where hydrophilic fibers are usually used, such as industrial wipers, waste liquid absorbing materials, filters, etc.

[0147] Example

[0148] The present invention is described below with reference to the following examples, but the present invention is not limited to the following examples. Hereinafter, unless otherwise specified, "parts" or "%" refer to "parts by weight" or "% by weight", respectively.

[0149] (1) Materials used

[0150] (1-1) Starch raw materials

[0151] Corn starch

[0152] Waxy corn starch

[0153] Cassava

[0154] (1-2) Hydrolase

[0155] α-Amylase (Spitase (registered trademark) HK / R manufactured by Nagase ChemteX Co., Ltd.), 12, 200 units / g

[0156] Amylomaltase: Thermus thermophilus was aerobically cultured, the crushed extract of the recovered cells was centrifuged, and the supernatant was used as a crude enzyme solution. The crude enzyme solution was subjected to column chromatography according to a conventional method, and the standard obtained by electrophoresis purification to a single substance was used as a purified enzyme solution.

[0157] It should be noted that the activity of amylomaltase is measured by the following method. A reaction solution containing 10 wt% maltotriose, 50 mM sodium acetate buffer (pH 6.0) and an enzyme is incubated at 60°C for 20 minutes. The reaction is then stopped by heating at 100°C for 10 minutes. The amount of glucose in the reaction solution is measured by the glucose oxidase method. Regarding the unit amount of amylomaltase, the amylomaltase activity that generates 1 μmol of glucose in 1 minute is taken as 1 unit.

[0158] (2) Production of Partially Degraded Starch Products (Production Examples 1 to 6)

[0159] The starch partial degradation product was prepared by the following method. It should be noted that the weight average molecular weight of the obtained starch partial degradation product was obtained based on a calibration curve of molecular weight and elution time prepared by pullulan with a known molecular weight in aqueous size exclusion chromatography. The weight average molecular weight and dispersity of the starch partial degradation product are shown in Table 1.

[0160] (Production Example 1) Partially Degraded Starch from Corn Starch

[0161] Corn starch was suspended in tap water at a concentration of 30% by weight, and then a 1N sodium hydroxide aqueous solution was added to adjust the pH to 6.0 to obtain starch milk. To the starch milk, 2.0 units of amylomaltase crude enzyme solution were added per 1 gram of starch solid matter, and after stirring at room temperature for 30 minutes, the mixture was reacted at 80°C for 6 hours under stirring to prepare liquefied starch. The weight average molecular weight of the obtained starch partial decomposition product was 6 million and the dispersity was 30.2.

[0162] (Production Example 2) Partially Degraded Starch from Corn Starch

[0163] Corn starch was suspended in tap water at a concentration of 30% by weight, and then a 1N sodium hydroxide aqueous solution was added to adjust the pH to 6.0 to obtain starch milk. To the starch milk, 0.1 units of amylomaltase crude enzyme solution was added per 1 gram of starch solid matter, and after stirring at room temperature for 30 minutes, the mixture was reacted at 90°C for 4.5 hours under stirring to prepare liquefied starch. The weight average molecular weight of the obtained starch partial decomposition product was 2.26 million and the dispersion degree was 14.9.

[0164] (Production Example 3) Partially Decomposed Starch from Cassava

[0165] The concentration of cassava was adjusted to 15% by weight, and 0.1 unit of amylomaltase crude enzyme solution was added per 1 gram of starch solid matter, and after stirring at room temperature for 30 minutes, the mixture was reacted at 80°C for 4 hours under stirring to prepare liquefied starch. The weight average molecular weight of the obtained starch partial degradation product was 1.18 million and the dispersion degree was 22.6.

[0166] (Production Example 4) Partially Decomposed Starch from Cassava

[0167] Liquefied starch was prepared by the same operation as in Production Example 3 except that the reaction time was changed to 12 hours. The weight average molecular weight of the obtained starch partial degradation product was 440,000 and the degree of dispersion was 17.3.

[0168] (Production Example 5) Partially Degraded Starch from Waxy Corn Starch

[0169] Waxy corn starch was suspended in tap water at a concentration of 15% by weight, and then adjusted to pH 6.0 by adding 1N sodium hydroxide aqueous solution to obtain starch milk. In the starch milk, 0.5 units of α-amylase were added per 1 gram of starch solid matter, and after stirring at room temperature for 30 minutes, the mixture was reacted at 100°C for 20 minutes under stirring to prepare liquefied starch. The weight average molecular weight of the obtained starch partial decomposition product was 610,000 and the dispersion degree was 35.2. The aqueous solution of the starch partial decomposition product was vacuum dried at 80°C, the obtained dry product was crushed, and a dry powder product passing through 1mm was recovered. The moisture content of the dry powder product was 4.8%.

[0170] (Production Example 6) Partially Degraded Starch from Corn Starch

[0171] Corn starch was suspended in tap water at a concentration of 30% by weight, and then a 1N sodium hydroxide aqueous solution was added to adjust the pH to 6.0 to obtain starch milk. To the starch milk, 0.2 units of amylomaltase crude enzyme solution was added per 1 gram of starch solid matter, and after stirring at room temperature for 30 minutes, the mixture was reacted at 90°C for 4.5 hours under stirring to prepare liquefied starch. The weight average molecular weight of the obtained starch partial decomposition product was 1.91 million and the dispersion degree was 10.1.

[0172] [Table 1]

[0173] Production Example 1 Production Example 2 Production Example 3 Production Example 4 Production Example 5 Production Example 6 Mw(million) 600 226 118 44 61 191 Dispersion 30.2 14.9 22.6 17.3 35.2 10.1

[0174] (3) Production of water-soluble polymers

[0175] (Production Example 7)

[0176] 140 g of the 30 wt% aqueous solution of the starch partial decomposition product prepared in Preparation Example 1 (the hydroxyl group of the starch partial decomposition product is 0.78 mol) is placed in a 500 ml separable flask equipped with a stirrer, a thermometer, and a condenser. Then, 37.6 g of a 48.8% sodium hydroxide aqueous solution (0.46 mol, 0.59 equivalent to the hydroxyl group of the starch partial decomposition product) is added, and the mixture is stirred at 60°C or below until the solution becomes completely uniform. After confirming that the solution becomes uniform, 20.6 g of monochloroacetic acid (0.44 mol, 0.8 equivalent to the hydroxyl group of the starch partial decomposition product) is dissolved in 5.2 g of ion exchange water, and the resulting aqueous solution is added dropwise at 50 to 60°C for 30 minutes. After the monochloroacetic acid aqueous solution is added, the temperature is adjusted to 45 to 50°C, and the mixture is stirred for 12 hours. Regarding the end point of the reaction, the reaction solution was sampled and the chloride ion content in the reaction solution was measured by potentiometric titration using a 0.01N silver nitrate aqueous solution, with the condition that the measured value reached 98% or more of the calculated value (3.8%) of the chloride ion content when all the monochloroacetic acid reacted. In this production example, the chloride content was 3.75%.

[0177] After the reaction is completed, the reaction solution is diluted with 600 g of ion exchange water. The diluted reaction solution is cooled to room temperature and added to 5000 ml of methanol in about 30 minutes to separate and reprecipitate the water-soluble polymer. After adding all the reaction solutions, the mixture is stirred for 30 minutes and the water-soluble polymer dispersed in the methanol is separated into solid and liquid by filtration under reduced pressure.

[0178] Next, in order to remove the sodium chloride contained in the water-soluble polymer, the recovered water-soluble polymer was redispersed in 1000 ml of aqueous methanol with a methanol / water ratio of 80 / 20 (volume ratio), stirred and washed at room temperature for 30 minutes, and then the solid-liquid separation was performed by vacuum filtration to recover the water-soluble polymer again. The chlorine content of the recovered water-soluble polymer was determined by potentiometric titration using a 0.01N silver nitrate aqueous solution, and the washing process was repeated until the chlorine content was less than 1%. The total acid value of the obtained water-soluble polymer was 128 mgKOH / g, the degree of etherification calculated from the total acid value was 0.45, the weight average molecular weight was 30.31 million, and the dispersion was 25.7.

[0179] (Production Example 8)

[0180] 200 g of a 30 wt% aqueous solution of the starch partial decomposition product prepared in Preparation Example 2 (1.11 mol of hydroxyl groups in the starch partial decomposition product) is placed in a 500 ml removable flask equipped with a stirrer, a thermometer, and a condenser. Then, 79.4 g of a 48.8% sodium hydroxide aqueous solution (0.96 mol, 0.86 equivalents relative to the hydroxyl groups in the starch partial decomposition product) is added, and the mixture is stirred at a temperature below 60°C until the solution becomes completely uniform. After confirming that the solution has become uniform, 89.9 g of 6-bromohexanoic acid (0.46 mol, 0.4 equivalents relative to the hydroxyl groups in the starch partial decomposition product) is added little by little at 50 to 60°C over a period of 30 minutes. After the 6-bromohexanoic acid is added, the temperature is adjusted to 45 to 50°C and stirred for 10 hours. Regarding the end point of the reaction, the reaction solution was sampled and the bromide ion content in the reaction solution was measured by potentiometric titration using a 0.01N silver nitrate aqueous solution, with the condition that the measured value reached 98% or more of the calculated value (9.8%) of the bromide ion content when all 6-bromohexanoic acid reacted. In this production example, the bromine content was 10.1%.

[0181] After the reaction is completed, the reaction solution is diluted with 250 g of ion exchange water. The diluted reaction solution is cooled to room temperature and added to 1600 ml of ethanol in about 30 minutes to separate out the water-soluble polymer and reprecipitate it. After adding all the reaction solutions, the mixture is stirred for 30 minutes and the water-soluble polymer dispersed in the ethanol is separated into solid and liquid by filtration under reduced pressure.

[0182] Next, in order to remove the sodium bromide contained in the water-soluble polymer, the recovered water-soluble polymer was redispersed in 500 ml of aqueous ethanol with an ethanol / water ratio of 90 / 10 (volume ratio), stirred and washed at room temperature for 30 minutes, and then the solid-liquid separation was performed by vacuum filtration to recover the water-soluble polymer again. The bromine content of the recovered water-soluble polymer was measured by potentiometric titration using a 0.01N silver nitrate aqueous solution, and the washing process was repeated until the bromide ion content was less than 1%. The total acid value of the obtained water-soluble polymer was 133 mgKOH / g, the degree of etherification calculated from the total acid value was 0.55, the weight average molecular weight was 10.42 million, and the dispersion was 24.7.

[0183] (Production Example 9)

[0184] 200 g of a 30 wt% aqueous solution of the starch partial decomposition product prepared in Preparation Example 3 (1.11 mol of hydroxyl groups of the starch partial decomposition product) was added to a 500 ml separable flask equipped with a stirrer, a thermometer, and a condenser. Then, 47.8 g of a 48.8% sodium hydroxide aqueous solution (0.58 mol, 1.1 equivalents to the hydroxyl groups of the starch partial decomposition product) was added, and the mixture was stirred at 60°C or below until the solution became completely uniform. After confirming that the solution became uniform, an aqueous solution prepared by dissolving 77.7 g of sodium monochloroacetate (0.67 mol, 1.2 equivalents to the hydroxyl groups of the starch partial decomposition product) in 111 g of water was added little by little at 50 to 60°C for 30 minutes. After the sodium monochloroacetate aqueous solution was added, the temperature was adjusted to 90 to 95°C, and the mixture was stirred for 5 hours. Regarding the end point of the reaction, the reaction solution was sampled and the chloride ion content in the reaction solution was determined by potentiometric titration using a 0.01N silver nitrate aqueous solution, with the condition that the measured value reached 98% or more of the calculated value (5.4%) of the chloride ion content when all the sodium monochloroacetate reacted. In this manufacturing example, the chloride content was 5.3%.

[0185] After the reaction was completed, the reaction solution was cooled to room temperature and added to 2000 ml of methanol over about 30 minutes to precipitate and reprecipitate the water-soluble polymer. After all the reaction solution was added, stirring was performed for 30 minutes, and the water-soluble polymer dispersed in the methanol was separated into solid and liquid by vacuum filtration.

[0186] Next, in order to remove the sodium chloride contained in the water-soluble polymer, the recovered water-soluble polymer was dispersed in 1000 ml of methanol again, stirred and washed at room temperature for 30 minutes, and then the solid-liquid separation was performed by vacuum filtration to recover the water-soluble polymer again. The chlorine content of the recovered water-soluble polymer was determined by potentiometric titration using a 0.01N silver nitrate aqueous solution, and the washing process was repeated until the chloride ion content was less than 1%. The total acid value of the obtained water-soluble polymer was 152 mgKOH / g, the degree of etherification calculated from the total acid value was 0.56, the weight-average molecular weight was 8.68 million, and the dispersion was 18.3.

[0187] (Production Example 10)

[0188] A water-soluble polymer was obtained by the same reaction and post-treatment as in Production Example 9 except that the starch partial decomposition product was changed to the starch partial decomposition product produced in Production Example 4. The obtained water-soluble polymer had a total acid value of 148 mgKOH / g, a degree of etherification calculated from the total acid value of 0.54, a weight average molecular weight of 3.07 million, and a degree of dispersion of 9.5.

[0189] (Production Example 11)

[0190] 50 g of the powder (water content 4.8%) of the starch partial decomposition product prepared in Preparation Example 5 (the hydroxyl group of the starch partial decomposition product is 0.88 mol) and 140 g of water are placed in a 1000 ml separable flask equipped with a stirrer, a thermometer, and a condenser. Then, 94.7 g of a 48.8% sodium hydroxide aqueous solution (1.2 mol, 1.3 equivalents to the hydroxyl group of the starch partial decomposition product) is added, and the mixture is stirred at 60°C or below until the solution becomes completely uniform. After confirming that the solution becomes uniform, an aqueous solution prepared by dissolving 154 g of sodium monochloroacetate (1.3 mol, 1.5 equivalents to the hydroxyl group of the starch partial decomposition product) in 300 g of water is added little by little at 50 to 60°C for 30 minutes. After the sodium monochloroacetate aqueous solution is added, the temperature is adjusted to 90 to 95°C, and the mixture is stirred for 5 hours. Regarding the end point of the reaction, the reaction solution was sampled and the chloride ion content in the reaction solution was measured by potentiometric titration using a 0.01N silver nitrate aqueous solution, with the condition that the measured value reached 98% or more of the calculated value (6.3%) of the chloride ion content when all the sodium monochloroacetate reacted. In this manufacturing example, the chloride content was 6.3%.

[0191] After the reaction was completed, the reaction solution was cooled to room temperature and added to 5000 ml of methanol over about 30 minutes to precipitate and reprecipitate the water-soluble polymer. After all the reaction solution was added, stirring was performed for 30 minutes, and the water-soluble polymer dispersed in the methanol was separated into solid and liquid by vacuum filtration.

[0192] Next, in order to remove the sodium chloride contained in the water-soluble polymer, the recovered water-soluble polymer was dispersed in 2000 ml of methanol again, stirred and washed at room temperature for 30 minutes, and then solid-liquid separation was performed by vacuum filtration to recover the water-soluble polymer again. The chlorine content of the recovered water-soluble polymer was determined by potentiometric titration using a 0.01N silver nitrate aqueous solution, and the washing process was repeated until the chloride ion content was less than 1%. The total acid value of the obtained water-soluble polymer was 192 mgKOH / g, the degree of etherification calculated from the total acid value was 0.76, the weight average molecular weight was 2.3 million, and the dispersion was 22.3.

[0193] (Production Example 12)

[0194] The reaction and post-treatment were carried out in the same manner as in Production Example 7, except that the starch partial decomposition product was changed to 140 g of the starch partial decomposition product produced in Production Example 6, the 48.8% sodium hydroxide aqueous solution was changed to 55.6 g (0.68 mol, 0.87 equivalents to the hydroxyl groups of the starch partial decomposition product), the monochloroacetic acid was changed to 30.5 g (0.32 mol, 0.4 equivalents to the hydroxyl groups of the starch partial decomposition product), and the ion exchange water in which the monochloroacetic acid was dissolved was changed to 8 g, to obtain an aqueous polymer. The obtained water-soluble polymer had a total acid value of 137 mgKOH / g, a degree of etherification calculated from the total acid value of 0.49, a weight average molecular weight of 11.89 million, and a degree of dispersion of 15.3.

[0195] (4) Production of water-absorbent resin

[0196] (Production Example 13)

[0197] 170 g of the water-soluble polymer obtained in Preparation Example 7 (wet product containing methanol, moisture content 69%) was placed in a 1000 ml beaker, and 550 ml of methanol containing methanol in a volume ratio of 80 / 20 (volume ratio) was further added to disperse the water-soluble polymer. 5.8 ml of a 1N hydrochloric acid aqueous solution was slowly added thereto using a graduated pipette while stirring with a magnetic stirrer. After adding the hydrochloric acid, the mixture was stirred for 15 minutes, and vacuum filtered to recover the water-soluble polymer partially neutralized to a free acid. The recovered water-soluble polymer was a wet crystal containing alcohol. The wet crystal was transferred to a plate, placed in a blast dryer set at 70°C, and dried for 20 hours to perform a crosslinking treatment. The solid obtained after the treatment was crushed with a mortar, sieved using a sieve with a mesh size of 150 μm and 850 μm, and particles of a water-absorbent resin with a particle size of 150 to 850 μm were recovered.

[0198] (Production Example 14)

[0199] 170 g of the water-soluble polymer obtained in Preparation Example 8 (wet product containing hydrous ethanol, moisture ratio 61%) was placed in a 1000 ml beaker, and 500 ml of ethanol was further added to disperse the water-soluble polymer. 82.2 ml of 1N hydrochloric acid aqueous solution was slowly added thereto with a graduated pipette while stirring with a magnetic stirrer. After adding hydrochloric acid, the mixture was stirred for 15 minutes, and vacuum filtered to recover the water-soluble polymer partially neutralized into free acid. The recovered water-soluble polymer is wet crystals containing hydrous alcohol. The wet crystals were transferred to a plate, placed in a blast dryer set at 150° C., dried for 1 hour, and cross-linked. The solid obtained after the treatment was crushed with a mortar, sieved using a sieve with a mesh size of 150 μm and 850 μm, and particles of water-absorbent resin with a particle size of 150 to 850 μm were recovered.

[0200] (Production Examples 15 to 21)

[0201] Except having changed into the raw material and charging amount shown in Table 2, the same operation as that of Production Example 13 was carried out, and the water-absorbent resin was obtained.

[0202]

[0203] (Comparative Manufacturing Example 1)

[0204] Production of water-absorbent resin composed of sodium polyacrylate

[0205] 155 parts by mass (2.15 parts by mole) of acrylic acid, 0.62 parts by mass (0.0024 parts by mole) of pentaerythritol triallyl ether as an internal crosslinking agent, and 340.27 parts by mass of deionized water were stirred and mixed while being kept at 1°C. Nitrogen was passed through the mixture to reduce the amount of dissolved oxygen to 0.1 ppm or less, and then 0.31 parts by mass of a 1% by mass hydrogen peroxide aqueous solution, 1.16 parts by mass of a 1% by mass ascorbic acid aqueous solution, and 2.325 parts by mass of a 0.5% by mass 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide] aqueous solution were added and mixed to initiate polymerization. After the temperature of the mixture reached 85°C, polymerization was performed at 85±2°C for about 10 hours to obtain a water-containing gel. Next, while 502.27 parts by mass of the hydrogel was shredded by a shredder (manufactured by ROYAL, "12VR-400K"), 128.42 parts by mass of a 48.5% by mass sodium hydroxide aqueous solution was added and mixed, and further 3 parts by mass of a 1% by mass aqueous solution of ethylene glycol diglycidyl ether was added and mixed to obtain a shredded gel. The shredded gel was further dried by a ventilated belt dryer {200°C, wind speed 5 m / sec} to obtain a dried body. The dried body was pulverized by a juicer blender (manufactured by Oster, "OSTERIZER BLENDER"), and then adjusted to a particle size of 150 μm to 710 μm using sieves with mesh sizes of 150 μm and 710 μm, thereby obtaining dried body particles.

[0206] (5)Manufacturing of diapers

[0207] (Examples 1 to 7)

[0208] A 100 mm × 133 mm water-absorbent resin / pulp mixed absorbent (basic weight of the pulp was 0.0375 g / cm2) was prepared by mixing 4 g of a water-absorbent resin and 5 g of wood pulverized pulp using a batch-type air papermaking apparatus. 2 , the basis weight of the water-absorbent resin is 0.03g / cm 2). The absorbent resin / pulp mixed absorbent was sandwiched between tissue paper and pressed 10 times with a 15 kg roller to obtain an absorbent layer. The absorbent layer was sandwiched between a thermal bonded nonwoven fabric (18 gsm) and a polyethylene sheet and fixed with tape to prepare a diaper sample. The absorbent resin used is shown in Table 3.

[0209] (Comparative Example 1)

[0210] A disposable diaper was produced by the same method as in Examples 1 to 7 except that the water-absorbent resin of Comparative Production Example 1 was used as the water-absorbent resin.

[0211] The absorption rate, rewet amount, and diffusion length of the disposable diaper were measured by the method described below. The results are shown in Table 3.

[0212]

[0213] In Examples 1 to 7, the absorption rate, rewet amount, and diffusion length all achieved sufficient performance for practical use as disposable diapers. In some examples, performance far exceeding that of Comparative Example 1 using conventional sodium polyacrylate was achieved.

[0214] (6) Manufacturing of sanitary napkins

[0215] (Examples 8 to 10)

[0216] Using a batch type air papermaking apparatus, 0.5 g of water-absorbent resin was used to prepare a 50 mm × 70 mm absorbent resin (the basis weight of the water-absorbent resin was 0.0143 g / cm 2 The absorbent body was sandwiched between thin paper sheets and pressed 10 times with a 15 kg roller to obtain an absorbent layer. The absorbent layer was sandwiched between polyethylene sheets and fixed around with tape to prepare a sanitary napkin sample. The water-absorbent resin used is shown in Table 4.

[0217] (Comparative Example 2)

[0218] A sanitary napkin was produced by the same method as in Examples 8 to 10 except that the water-absorbent resin of Comparative Production Example 1 was used as the water-absorbent resin.

[0219] The absorption rate, rewet amount, absorption amount, and water retention of the sanitary napkin were measured by the methods described below. The results are shown in Table 4.

[0220]

[0221] In Examples 8 to 10, the absorption rate, rewet amount, absorption amount, and water retention amount all achieved performances exceeding those of Comparative Example 2 using the existing sodium polyacrylate.

[0222] (7) Evaluation method of water-soluble polymers

[0223] (7-1) Total acid value of water-soluble polymer

[0224] Accurately weigh about 0.3g of a water-soluble polymer in a 100ml beaker and dissolve it with 40ml of ion exchange water. The aqueous solution is placed in a potentiometric titration apparatus (AT-610 manufactured by Kyoto Electronics Co., Ltd.) equipped with a glass electrode (C-171 manufactured by Kyoto Electronics Co., Ltd.). In the case where the sample is all sodium salt, at this stage, the potential is roughly below 30mV, so a 1N hydrochloric acid aqueous solution is added until the potential reaches 320mV or more, so that all the carboxylic acid groups in the water-soluble polymer become free acid states (become a state of excess hydrochloric acid). Confirm that the potential has reached more than 320mV, and use a 0.1N sodium hydroxide aqueous solution for neutralization titration. In this titration, two inflection points are detected, the first inflection point is detected near 220mV, and the second inflection point is detected near 0 to -30mV. The former is the neutralization point of the excess hydrochloric acid in the sample, and the latter is the neutralization point of the carboxylic acid in the water-soluble polymer. Therefore, the total acid value is calculated by the following formula 1.

[0225] Total acid value (mgKOH / g) = [{(Vb-Va)×0.1×fa×56.11}÷Sa] / (1-wr) (Formula 1)

[0226] Here, Va is the volume (ml) of the 0.1N sodium hydroxide aqueous solution consumed until the first inflection point, Vb is the volume (ml) of the 0.1N sodium hydroxide aqueous solution consumed until the second inflection point, fa is the titer (power) of the 0.1N sodium hydroxide aqueous solution, Sa is the sample collection amount, and Wr is the moisture content of the water-soluble polymer measured by the method described below.

[0227] (7-2) Moisture content of water-soluble polymer

[0228] The moisture ratio refers to the ratio (%) of the weight reduction of the sample when it is dried at a drying temperature of 130°C using a halogen moisture meter relative to the initial weight of the sample. In this embodiment, 0.5 to 1.0 g of a water-soluble polymer is placed in a halogen moisture meter HC103 manufactured by Mettler Toredo Co., Ltd., and the measurement is performed under the conditions of a drying temperature of 130°C, a shutdown standard of 1 mg / 50 seconds, and a %MC mode (a mode in which the displayed MC value = (initial weight of the sample - drying weight) ÷ initial weight of the sample × 100). The displayed MC value is taken as the moisture ratio.

[0229] (7-3) Degree of etherification of water-absorbent resin

[0230] Degree of etherification = (162×TAV) ÷ (56100-80×TAV)

[0231] Here, TAV is the total acid value of the water-soluble polymer (unit: mgKOH / g).

[0232] (8) Evaluation method of diapers

[0233] (8-1) Absorption rate

[0234] The diaper was placed on a horizontal surface with the top sheet facing upward, and an acrylic plate with a tube (weight 200 g) was placed in the center for measurement. 25 g of saline solution (salt concentration 0.9 wt%) was poured into the cylinder in the center at once. The time required for the saline solution in the tube to be absorbed into the diaper was measured and taken as the absorption rate.

[0235] (8-2) Re-seepage

[0236] After the absorption rate test, the test was left for 5 minutes, then the acrylic plate with a tube for measurement was removed, and about 20 g of filter paper (accurately weighed as W1 (g)) was placed, and a 3.5 kg weight was further placed, and pressure was applied for 3 minutes. After 3 minutes, the filter paper was removed and its weight was measured (W2 (g)). The re-seepage amount was calculated by the following formula.

[0237] Re-seepage amount (g) = W2-W1

[0238] (8-3) Diffusion length

[0239] The operation of (8-1) absorption rate and (8-2) rewet amount was repeated two more times, and the measurement was performed three times in total. The diffusion length (maximum length) of the physiological saline on the disposable diaper was measured.

[0240] (9) Evaluation method of sanitary napkins

[0241] (9-1) Absorption

[0242] The sanitary napkin was immersed in 1000 ml of milk for 1 hour without stirring, and then hung for 10 minutes to remove water. The weight (h5) was measured and the absorption amount was calculated from the following formula. It should be noted that the temperature of the milk used and the measurement atmosphere was 25°C ± 2°C.

[0243] Absorption (g / piece) = (h5) - (h6)

[0244] It should be noted that (h6) is the weight of the sanitary napkin before impregnation.

[0245] (9-2)Water retention capacity

[0246] After the absorption test, the milk was placed in a centrifuge and dehydrated at 150 G for 120 seconds to remove excess milk. The weight (h7) was measured and the water retention was calculated using the following formula.

[0247] Water retention (g / tablet) = (h7) - (h6)

[0248] (9-3) Absorption rate

[0249] Place the sanitary napkin on a horizontal surface with the top sheet facing up, place a cylindrical acrylic tool (weight 200g) for measurement in the center, and pour 5g of milk into the cylinder in the center at once. The time required for the milk in the cylinder to be absorbed into the sanitary napkin is measured and taken as the absorption rate.

[0250] (9-4) Re-seepage

[0251] After the absorption rate test, the test was left for 5 minutes, then the cylindrical acrylic tool for measurement was removed, and about 20g of filter paper (accurately weighed as W1(g)) was placed, and a 0.5kg weight was further placed, and pressure was applied for 3 minutes. After 3 minutes, the filter paper was removed and its weight was measured (W2(g)). The re-seepage amount was calculated by the following formula.

[0252] Re-seepage amount (g) = W2-W1

[0253] (10) Decomposition and regeneration of water-absorbent resin

[0254] (10-1) Manufacturing of Diapers

[0255] (10-1-1) Production of partially decomposed starch from cassava (Production Example 22)

[0256] Tapioca starch was suspended in tap water at a concentration of 30% by weight, and then adjusted to pH 6.0 by adding a 1N sodium hydroxide aqueous solution to obtain starch milk. To the starch milk, 8.0 units of amylomaltase crude enzyme solution were added per 1 gram of starch solid matter, and after stirring at room temperature for 30 minutes, the mixture was reacted at 80°C for 5 hours under stirring to prepare liquefied starch. The weight average molecular weight of the obtained starch partial decomposition product was 2.82 million and the dispersion degree was 9.82.

[0257] (10-1-2) Production of water-soluble polymer (Production Example 23)

[0258] 140 g of a 30 wt% aqueous solution of the starch partial decomposition product of Production Example 22 (0.78 mol of hydroxyl groups of the starch partial decomposition product) was placed in a 500 ml separable flask equipped with a stirrer, a thermometer, and a condenser. Then, 37.6 g of a 48.8% sodium hydroxide aqueous solution (0.46 mol, 0.59 equivalents to the hydroxyl groups of the starch partial decomposition product) was added, and the mixture was stirred at 60°C or below until the solution became completely uniform. After confirming that the solution became uniform, an aqueous solution prepared by dissolving 20.6 g of monochloroacetic acid (0.44 mol, 0.8 equivalents to the hydroxyl groups of the starch partial decomposition product) in 5.2 g of ion exchange water was added dropwise at 60-70°C for 30 minutes. After the monochloroacetic acid aqueous solution was added, the temperature was adjusted to 80-90°C, and the mixture was stirred for 1 hour. Regarding the end point of the reaction, the reaction solution was sampled and the chloride ion content in the reaction solution was measured by potentiometric titration using a 0.01N silver nitrate aqueous solution, with the condition that the measured value reached 98% or more of the calculated value (3.8%) of the chloride ion content when all the monochloroacetic acid reacted. In this production example, the chloride content was 3.81%.

[0259] After the reaction is completed, the reaction solution is diluted with 600 g of ion exchange water. The diluted reaction solution is cooled to room temperature and added to 5000 ml of methanol in about 30 minutes to separate and reprecipitate the water-soluble polymer. After adding all the reaction solutions, the mixture is stirred for 30 minutes and the water-soluble polymer dispersed in the methanol is separated into solid and liquid by filtration under reduced pressure.

[0260] Next, in order to remove the sodium chloride contained in the water-soluble polymer, the recovered water-soluble polymer is dispersed in 1000 ml of aqueous methanol with a methanol / water ratio of 80 / 20 (volume ratio), stirred and washed at room temperature for 30 minutes, and then solid-liquid separation is performed by vacuum filtration to recover the water-soluble polymer again. The chlorine content of the recovered water-soluble polymer is determined by potentiometric titration using a 0.01N silver nitrate aqueous solution, and the washing process is repeated until the chlorine content is less than 1%. The total acid value of the obtained water-soluble polymer is 131.7 mgKOH / g, the weight-average molecular weight is 9.42 million, and the dispersion is 15.3.

[0261] (10-1-3) Production of water-absorbent resin (Production Example 24)

[0262] 170 g of the water-soluble polymer obtained in Preparation Example 23 (wet product containing methanol, moisture content 68%) was placed in a 1000 ml beaker, and 550 ml of methanol containing methanol / water = 80 / 20 (volume ratio) was further added to disperse the water-soluble polymer. 10.5 ml of 1N hydrochloric acid aqueous solution was slowly added thereto with a graduated pipette while stirring with a magnetic stirrer. After adding hydrochloric acid, the mixture was stirred for 15 minutes, and vacuum filtered to recover the water-soluble polymer partially neutralized into free acid. The recovered water-soluble polymer is wet crystals containing alcohol. The wet crystals were transferred to a plate, placed in a blast dryer set at 70°C, and dried for 20 hours to perform a crosslinking treatment. The solid obtained after the treatment was crushed with a mortar, sieved with a mesh of 150 μm and 850 μm, and particles of water-absorbent resin with a particle size of 150 to 850 μm were recovered.

[0263] Production of water-absorbent resin composed of sodium polyacrylate (Comparative Production Example 2)

[0264] 155 parts by mass (2.15 parts by mole) of acrylic acid, 0.62 parts by mass (0.0024 parts by mole) of pentaerythritol triallyl ether as an internal crosslinking agent, and 340.27 parts by mass of deionized water were stirred and mixed while being kept at 1°C. Nitrogen was passed through the mixture to reduce the amount of dissolved oxygen to 0.1 ppm or less, and then 0.31 parts by mass of a 1% by mass hydrogen peroxide aqueous solution, 1.16 parts by mass of a 1% by mass ascorbic acid aqueous solution, and 2.325 parts by mass of a 0.5% by mass 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide] aqueous solution were added and mixed to initiate polymerization. After the temperature of the mixture reached 85°C, polymerization was performed at 85±2°C for about 10 hours to obtain a water-containing gel. Next, while 502.27 parts by mass of the hydrogel was shredded by a shredder (manufactured by ROYAL, "12VR-400K"), 128.42 parts by mass of a 48.5% by mass sodium hydroxide aqueous solution was added and mixed, and further 3 parts by mass of a 1% by mass aqueous solution of ethylene glycol diglycidyl ether was added and mixed to obtain a shredded gel. The shredded gel was further dried by a ventilated belt dryer {200°C, wind speed 5 m / sec} to obtain a dried body. The dried body was pulverized by a juicer blender (manufactured by Oster, "OSTERIZER BLENDER"), and then adjusted to a particle size of 150 μm to 710 μm using sieves with mesh sizes of 150 μm and 710 μm, thereby obtaining dried body particles.

[0265] (10-1-4) Production of Diapers (Example 11)

[0266] 5.0 g of the water-absorbent resin obtained in Preparation Example 24 was placed on 5.0 g of a 10×40 cm pulp water-absorbent sheet, and the pulp water-absorbent sheet was folded in half to form a 10×20 cm, thereby preparing a water-absorbent resin / pulp mixed absorbent. The water-absorbent resin / pulp mixed absorbent was sandwiched between tissue paper on the top and bottom, and pressed back and forth 10 times with a 15 kg roller to obtain an absorbent layer. The absorbent layer was sandwiched between a top sheet (hot air nonwoven fabric (18 gsm)) and a back sheet (polyethylene sheet), and the periphery was fixed with tape to prepare a diaper sample.

[0267] (10-1-5) Production of disposable diapers (Comparative Example 3)

[0268] A disposable diaper was produced by the same method as in Example 11 except that the water-absorbent resin obtained in Comparative Production Example 2 was used instead of the water-absorbent resin obtained in Production Example 24.

[0269] (10-1-6) Absorption capacity of diapers

[0270] 40 ml of saline solution was applied to the diapers of Example 11 and Comparative Example 3 three times at 5-minute intervals to absorb a total of 120 ml. All diapers were able to absorb a total of 120 ml of saline solution. The saline solution used and the measurement atmosphere were at a temperature of 25°C ± 2°C.

[0271] (10-1-7) Water retention of diapers

[0272] After the absorption test, the diaper was placed in a centrifuge and centrifuged at 150G for 120 seconds to remove excess saline and measure the weight. The water retention was calculated by subtracting the weight before water absorption from the measured weight. The results showed that Example 11 was 106.5 g / piece and Comparative Example 3 was 111.9 g / piece.

[0273] (10-2) Decomposition of water-absorbent resin (Production Example 25)

[0274] The water-absorbent resin / pulp mixed absorbent body was taken out from the disposable diaper of Example 11 after the water retention capacity was measured, and immersed in 1000 ml of a sodium hydroxide aqueous solution (concentration 0.5 wt%) at 25°C ± 2°C for 30 minutes.

[0275] The solid residue of the absorbent was washed with water and centrifuged for dehydration, and then the ash content was measured in accordance with JIS P8251:2003 "Paper, paperboard and pulp - Ash content test method - 525°C combustion method". When all the water-absorbent resin remained in the solid residue of the absorbent, it was estimated that the ash content was about 6% due to the presence of sodium in the sodium hydroxide aqueous solution used in the production of the water-soluble polymer.

[0276] For comparison, the ash content of unused pulp was measured and the result was -0.7%. The theoretical value of ash content in unused pulp is 0, and the measured value is estimated to be within the error range. In contrast, the ash content in the solid residue of the absorbent was measured to be 0.8%, which is equivalent to the ash content of unused pulp. This result confirms that the water-absorbent resin contained in the absorbent is almost completely decomposed by the alkali treatment.

[0277] After the water-absorbent resin / pulp mixed absorbent was immersed in a sodium hydroxide aqueous solution, the decomposed product of the water-absorbent resin was present in the aqueous solution in the form of a regenerated water-soluble polymer. The recovered regenerated water-soluble polymer was analyzed by GPC and IR and compared with the unused water-soluble polymer obtained in Production Example 23. The results are shown in Figures 1-2 In addition, the molecular weight and dispersion are shown in Table 5. Figures 1-2 As shown, the molecular weight distribution and chemical structure of the regenerated water-soluble polymer contained in the decomposition product of the water-absorbent resin are equivalent to those of the unused water-soluble polymer.

[0278] [Table 5]

[0279]

[0280] (10-3) Regeneration of water-absorbent resin from decomposition products

[0281] To the aqueous solution containing the regenerated water-soluble polymer from the decomposition product obtained in Preparation Example 25 (weight 427g, solid content 1.4% by weight, alkali content 26.1meg / g) was added dropwise hydrochloric acid to neutralize and adjust the pH to 7-8. Water was distilled off using an evaporator until the solid content reached 10% by weight. It was reprecipitated in methanol, and 10.5g of the wet product of the regenerated water-soluble polymer (solid content 39.6%, net content 4.2g) was recovered by vacuum filtration. 300ml of aqueous methanol with methanol / water = 80 / 20 (volume ratio) was added to the recovered wet product of the regenerated water-soluble polymer to disperse the regenerated water-soluble polymer. While stirring with a magnetic stirrer, 0.8ml of a 1N hydrochloric acid aqueous solution was slowly added thereto with a graduated pipette. After adding the hydrochloric acid, it was stirred for 15 minutes, and vacuum filtration was performed to recover the regenerated water-soluble polymer that was partially neutralized into a free acid. The recovered regenerated water-soluble polymer was transferred to a petri dish, placed in a blower dryer set at 70°C, and dried for 20 hours to perform a crosslinking treatment. The solid obtained after the treatment was crushed in a mortar, sieved using sieves with meshes of 150 μm and 850 μm, and particles of water-absorbent resin with a particle size of 150 to 850 μm were recovered. The water absorption properties of the water-absorbent resin and the water-absorbent resin produced from unused water-soluble polymer by the same method are shown in Table 6.

[0282] [Table 6]

[0283]

[0284] As shown in Table 6, sufficient water absorption properties were obtained also when the water-absorbent resin was produced again from the regenerated water-soluble polymer which was the decomposition product of the water-absorbent resin.

[0285] (10-4) Recovery of Pulp (Production Examples 26 and 27, Comparative Production Examples 3 and 4)

[0286] The solid residue (recovered pulp) of the absorbent recovered by the alkali treatment of the absorbent in Manufacturing Example 25 was dried at 120°C using a blower dryer and then fiberized. The fiberized recycled pulp or virgin pulp was used in combination with the absorbent resin shown in Table 7 to prepare a disposable diaper having the same structure as in Example 11, and the water absorption rate and rewet amount were evaluated. The results are shown in Table 7.

[0287] [Table 7]

[0288]

[0289] As shown in Table 7, when the recycled pulp was used, performance equivalent to that of virgin pulp was obtained. It was confirmed that the recycled pulp can be used for the production of water-absorbent articles in the same manner as virgin pulp.

Claims

1. An absorbent article comprising a water-absorbent resin, the water-absorbent resin being composed of a water-soluble polymer obtained by introducing an acidic group into starch or a partial decomposition product thereof.

2. The absorbent article according to claim 1, wherein The acidic group is a carboxyalkyl group, a carboxyalkenyl group or a sulfoalkyl group.

3. The absorbent article according to claim 1 or 2, wherein: The starch or a partial decomposition product thereof has a weight average molecular weight (Mw) of 7.5 million or less and / or a dispersion degree (weight average molecular weight (Mw) / number average molecular weight (Mn)) of 5 or more.

4. The absorbent article according to any one of claims 1 to 3, wherein The pullulan-equivalent weight average molecular weight (Mw) of the water-soluble polymer obtained by aqueous size exclusion chromatography analysis is 500,000 to 40,000,000.

5. The absorbent article according to any one of claims 1 to 4, wherein The water-absorbent resin has the following characteristics: (a) the water absorption capacity of ion exchange water without pressure is 100 g / g to 500 g / g; (b) The water retention rate of ion exchange water is 80 g / g to 300 g / g; (c) the water absorption capacity of physiological saline under no pressure is 10 g / g to 70 g / g; and / or (d) The water retention rate of physiological saline is 5g / g to 60g / g.

6. The absorbent article according to any one of claims 1 to 5, wherein The absorbent article is any one selected from the group consisting of sanitary products, medical products, food preservation products, civil engineering products, and agricultural and gardening products.

7. The absorbent article according to claim 6, wherein: The sanitary product is any one selected from the group consisting of diapers, sanitary products, incontinence pads, breast milk pads, portable toilets, and pet toilets.

8. The absorbent article according to claim 6, wherein: The medical product is any one selected from the group consisting of a hemostatic sponge, a wound protection material, a wound healing material, a medical waste solidifying agent, a cooling agent, a carrier for a drug delivery system, and an artificial joint. 9 . A regenerated water-soluble polymer obtained by subjecting the absorbent article according to claim 1 to an alkali treatment.

10. A water-absorbent resin which is a cross-linked product of the regenerated water-soluble polymer according to claim 9.

11. A water-absorbent article comprising the water-absorbent resin according to claim 10.

12. A method for recovering hydrophilic fibers from an absorbent article comprising a water-absorbent resin and hydrophilic fibers, wherein the water-absorbent resin is composed of a water-soluble polymer obtained by introducing acidic groups into starch or a partially decomposed product thereof, wherein: This method includes a step of subjecting a part or the whole of the water-absorbent article to an alkali treatment to decompose the water-absorbent resin.

Citation Information

Patent Citations

  • Manufacturing method for starch based water absorbent material

    JP2007222704A

  • Superabsorbent surface-treated carboxyalkylated polysaccharides and their manufacturing method

    JP2010504414A

  • Method for making absorbent starch

    US5079354A